2016
DOI: 10.1088/1367-2630/18/10/103019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamos in precessing cubes

Abstract: We investigate with numerical simulations the dynamo properties of liquid flows in precessing cubes. There are some similarities with the flow in precessing spheres. Instabilities in the form of triad resonances are observed. The flow is turbulent far above the onset of instability but simplifies to a single vortex for certain control parameters. The critical magnetic Reynolds numbers for the onset of magnetic field generation are lower than, but comparable to, the numbers known for precessing spheres, and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Ekman pumping at the boundaries and triad resonances were the first to be observed (Tilgner 2005). Dynamos in long slender vortices which form at low Ekman numbers were found later (Goepfert and Tilgner 2016). Recently (Giesecke et al 2018), it was shown that for certain parameters, the flow in precessing cylinders resembles the s 2 t 1 flow studied by Dudley and James (1989) as kinematic dynamo in a sphere.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Ekman pumping at the boundaries and triad resonances were the first to be observed (Tilgner 2005). Dynamos in long slender vortices which form at low Ekman numbers were found later (Goepfert and Tilgner 2016). Recently (Giesecke et al 2018), it was shown that for certain parameters, the flow in precessing cylinders resembles the s 2 t 1 flow studied by Dudley and James (1989) as kinematic dynamo in a sphere.…”
Section: Resultsmentioning
confidence: 91%
“…There are several reasonable options for removing dimensions from the governing equations. Here, we adopt the choice already made in Goepfert and Tilgner (2016) and base the unit of time on the total angular frequency of rotation about the container axis, denoted as x-axis, to which bothω D andΩ P contribute. The unit of time is then 1/(ω D +Ω P cos α) and the nondimensional rotation rates ω D and Ω P derived formω D andΩ P are…”
Section: The Mathematical Model Of a Precessing Cubementioning
confidence: 99%
See 1 more Smart Citation
“…Defining Ω o = Ω s + Ω p , we choose Ω −1 o as the unit of time such that it remains relevant in both limits of large Ω s or large Ω p (see also Goepfert & Tilgner, 2016). We choose R and RΩ o √ µρ as the respective units of length and magnetic field.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Gans 1970;Meunier et al 2008;Herault et al 2015), the cube (e.g. Goepfert & Tilgner 2016), the sphere (e.g. Kida 2011;Boisson et al 2012;Goto et al 2014;Lin et al 2015), the spherical shell (e.g.…”
Section: Introductionmentioning
confidence: 99%